2021
DOI: 10.1016/s2468-2667(21)00200-0
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic and worldwide organ transplantation: a population-based study

Abstract: Background Preliminary data suggest that COVID-19 has reduced access to solid organ transplantation. However, the global consequences of the COVID-19 pandemic on transplantation rates and the effect on waitlisted patients have not been reported. We aimed to assess the effect of the COVID-19 pandemic on transplantation and investigate if the pandemic was associated with heterogeneous adaptation in terms of organ transplantation, with ensuing consequences for waitlisted patients.Methods In this population-based,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
179
1
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 179 publications
(197 citation statements)
references
References 35 publications
5
179
1
12
Order By: Relevance
“…The impact on solid organ transplantation has been particularly marked, with many countries reporting significantly fewer organ donors and organ transplants. 1 - 3 Furthermore, organ transplant recipients are more likely to die after SARS-CoV-2 infection than the general population. 4 …”
Section: Introductionmentioning
confidence: 99%
“…The impact on solid organ transplantation has been particularly marked, with many countries reporting significantly fewer organ donors and organ transplants. 1 - 3 Furthermore, organ transplant recipients are more likely to die after SARS-CoV-2 infection than the general population. 4 …”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 virus was recognized worldwide by the World Health Organization in 2020, and the virus was able to spread rapidly worldwide [ 1 ]. So far, more than 98 million people have been infected with COVID-19, resulting in nearly 2.2 million deaths [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pandemia affected not only public health but also health-care services worldwide. A cohort study in 22 countries reported an overall decrease of 15.92% of organ transplantation in 2020 compared to 2019 (Aubert et al 2021 ). In Italy, organ transplantations in 2020 were 10% less than in 2019, while tissue transplantation was 20% decreased ( www.trapianti.salute.gov.it ).…”
Section: Introductionmentioning
confidence: 99%